2016
DOI: 10.4338/aci-2016-05-ra-0075
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Longitudinal Assessment of Ophthalmologists’ Perceptions after Implementing an Electronic Health Record System

Abstract: SummaryObjectives: To understand the attitudes and perceptions of ophthalmologists toward an electronic health record (EHR) system, before and after its clinical implementation. Methods: Ophthalmologists at a single large academic ophthalmology department were surveyed longitudinally before and after implementation of a new EHR system. The survey measured ophthalmologists' attitudes toward implementation of a new EHR. Questions focused on satisfaction, efficiency, and documentation. All attending physicians (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
(24 reference statements)
0
19
0
1
Order By: Relevance
“…1,4,7,[12][13][14][15][16] One longitudinal study conducted in an academic ophthalmology department over 2 years before and after EHR implementation demonstrated that ophthalmologists were significantly more likely to express concern about the impact of an EHR on meaningful patient interaction after implementation. 17 One strategy to address these issues has focused on redesigning EHRs, with multiple studies examining how to improve EHR usability, optimize user interfaces, and reduce click burden. 8,[18][19][20][21][22][23] However, executing EHR design changes can be constrained by limitations imposed by institutional infrastructure or by EHR vendors.…”
Section: Background and Significancementioning
confidence: 99%
“…1,4,7,[12][13][14][15][16] One longitudinal study conducted in an academic ophthalmology department over 2 years before and after EHR implementation demonstrated that ophthalmologists were significantly more likely to express concern about the impact of an EHR on meaningful patient interaction after implementation. 17 One strategy to address these issues has focused on redesigning EHRs, with multiple studies examining how to improve EHR usability, optimize user interfaces, and reduce click burden. 8,[18][19][20][21][22][23] However, executing EHR design changes can be constrained by limitations imposed by institutional infrastructure or by EHR vendors.…”
Section: Background and Significancementioning
confidence: 99%
“…Physicians reported that the EHR created additional work and their satisfaction dropped [ 9 ]. In a similarly-designed study, ophthalmologists did not report a significant change in overall job satisfaction over time (3, 7, 13, and 24 months post-EHR implementation), but they expressed concern about the EHR’s effect on interactions with patients and their ability to create quality documentation [ 10 ]. In primary care, even two years after EHR implementation, the EHR learning curve and computer knowledge remained challenging for interprofessional staff [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In der Augenheilkunde ist der Bedarf einer geordneten, übersichtlichen und vollständigen Darstellung der unterschiedlichsten Untersuchungen und Befunde besonders groß [4]. Die hohe Zahl an Patientenkontakten sowie die Häufung chronischer und komplexer Krankheitsverläufe machen eine schnelle Orientierung in der Patientenakte unverzichtbar.…”
Section: Hintergrundunclassified